Penggunaan Kurikulum 2013 Pembelajaran Seni Budaya (Musik) Di SMP Negeri 10 Kerinci Provinsi Jambi - Fadel Muhammad Iqbal; Harisnal Hadi (FBS Universitas Negeri Padang, 2020)
This research aims to describe the implementation of the 2013 curriculum on Music Art learning in the 10 Kerinci Junior high school, including soft-skill and hard-skill learning. The study uses theories related to the 2013 curriculum. The type of research used is qualitative research with descriptive methods of analysis. The object of this study was the study of musical art in class VIII SMP Negeri 10 kerinches on the Semetereven school year 2019/2020. Research instruments are self-research, namely in AIDS with the instruments of notebooks and observations with the technique of collecting observation data, interviews and library studies. The results showed that the teachers were able to music art of junior high School 10 Kerinci has been able to spread the concept of soft-skills and hard-skills well in the learning of music art in class VIII. As a BETUK application of the 2013 curriculum that succeeded characters, but does not overlook the purpose of learning knowledge and skills. Based on the results of the study, explained that whether or not the use of the curriculum 2013 and accompanying teaching devices, depends on the teacher's personal, especially in good faith and its codifying in explaining a curriculum. The 2013 curriculum which is based on soft-skill and hard-skill, will be successful or not, not because the curriculum are less precise or great, to the extent that the teacher understands with the intent of the 2013 curriculum that is involved in learning in the classroom.